Some Features of Composite Formation and Classification of Composites in Russian Language - Madaminova Nargiza Rajapbayevna (International Journal on Integrated Education, 2022)
This article touches upon the problems of Russian word formation. The issues related to one of the productive ways of word formation - word composition (compositing) are revealed. The definitions of the definitions of a compound word and a composite from different sources and from different authors are given. The classification of composites is described in detail.